ANTIHYPERTENSIVE EFFICACY OF CANDESARTAN IN PATIENTS WITH ARTERIAL HYPERTENSION (World Bulletin of Public Health, 2023)
The benefits of lowering blood pressure (BP) to achieve and maintain target levels to reduce the risk of cardiovascular morbidity and mortality are well established. The renin-angiotensin system plays an important role in the regulation of blood pressure and is a target for some groups of antihypertensive drugs, including AT1 receptor blockers for angiotensin P., which include candesartan. Candesartan 8-32 mg 1 time / day is recommended for the treatment of adult patients with arterial hypertension (AH). Candesartan has been shown in many randomized clinical trials to be effective in reducing the risk of cardiovascular mortality, stroke, heart failure, arterial stiffness, renal failure, retinopathy and migraine in various adult patient populations, including patients with concomitant type 2 diabetes mellitus, metabolic syndrome or impaired renal function. Available data indicate that candesartan is a highly effective drug for the treatment of hypertension.
Keywords: angiotensin receptor blockers; candesartan; arterial hypertension